Total synthesis of polycephalin C and determination of the absolute configurations at the 3",4" ring junction. - Longbottom, D; Morrison, A; Dixon, D; Ley, S (2002)
Only through total synthesis could the absolute configuration of the 3′′R,4′′R ring junction of the polyenoltetramic acid polycephalin C (1) be unambiguously established. Key features of the synthesis include a double Swern oxidation, double Stille coupling, and a double Takai olefination.